Gold‐Catalyzed Intramolecular Tandem Cyclization of Alkynol‐Tethered Alkylidenecyclopropanes to Construct Naphthalene‐Fused Eight‐ to Eleven‐Membered Cyclic Ethers. Issue 22 (26th October 2021) - Tao, Leyi; Wei, Yin; Shi, Min
Abstract: A gold‐catalyzed intramolecular tandem cyclization of alkynol‐tethered alkylidenecyclopropanes was reported in this paper, providing a synthetic route to access naphthalene‐fused eight‐ to eleven‐membered cyclic ether derivatives in moderate to good yields. On the basis of control experiments and DFT calculations, a reasonable reaction mechanism involving a gold carbene intermediate was proposed, which was formed via the 6‐endo‐dig enyne cyclization process. Abstract :